Impact of Telestroke Implementation on Emergency Department Transfer Rate. (19th April 2022) - Lyerly, Michael J.; Daggy, Joanne; LaPradd, Michelle; Martin, Holly; Edwards, Brandon; Graham, Glenn; Martini, Sharyl; Anderson, Jane; Williams, Linda S.
Abstract : Background and Objectives: Telestroke networks are associated with improved outcomes from acute ischemic stroke (AIS) and facilitate greater access to care, particularly in underserved regions. These networks also have the potential to influence patient disposition through avoiding unnecessary interhospital transfers. This study examines the effect of implementation of the VA National Telestroke Program (NTSP) on interhospital transfer among Veterans. Methods: We analyzed patients with AIS presenting to the emergency departments of 21 VA hospitals before and after telestroke implementation. Transfer rates were determined through review of administrative data and chart review and patient and facility-level characteristics were collected to identify predictors of transfer. Comparisons were made using t test, Wilcoxon rank sum, and χ 2 analysis. Multivariable logistic regression with sensitivity analysis was conducted to assess the influence of telestroke implementation on transfer rates. Results: We analyzed 3, 488 stroke encounters (1, 056 pre-NTSP and 2, 432 post-NTSP). Following implementation, we observed an absolute 14.4% decrease in transfers across all levels of stroke center designation. Younger age, higher stroke severity, and shorter duration from symptom onset were associated with transfer. At the facility level, hospitals with lower annual stroke volume were more likely to transfer; 1 hospital saw an increase in transfer rates following implementation. After adjusting for patient and facility characteristics, the implementation of VA NTSP resulted in a nearly 60% reduction in odds of transfer (odds ratio 0.39 [0.19, 0.77]). Discussion: In addition to improving treatment in acute stroke, telestroke networks have the potential to positively affect the efficiency of interhospital networks through disposition optimization and the avoidance of unnecessary transfers.